Impacting and being impacted by overuse injuries: an ethnodrama of parents' experiences. Issue 1 (2nd January 2022) - Cavallerio, Francesca; Wadey, Ross; Wagstaff, Christopher R. D.
ABSTRACT: The aim of this study was to explore the experience of parents of gymnasts suffering from overuse injuries. The work is part of a wider ethnographic project, with 43 participants (16 gymnasts, 3 coaches, 1 physiotherapist, 22 parents, 1 manager), which investigated the psychosocial factors affecting the development of overuse injuries in gymnasts. Data collection began with observations, formal and informal interviews, and a focus group, which were transcribed and analysed using reflective thematic analysis. Preliminary results were shared with the participants and reflective interviews were conducted to ensure depth and methodological rigour. Five themes were identified: ' Catch 22 ', highlighting the helplessness parents experienced watching their injured daughters; ' I (need to) trust these people ', referring to the parent–coach relationship; ' Because a gymnast cannot rest for too long ', which reconnects to aspects of Nixon's culture of risk; ' It's on me ', and ' Walking on a thin line ', two themes related to the sense of responsibility and the role of 'mediator' parents needed to adopt when dealing with their daughters' overuse injuries. Findings from the study are presented using ethnodrama, a form of creative analytical practice aiming to create an informative and evocative experience. This study extends existing research which has demonstrated a recent shift away from the simplistic perspective of sport parents being either good or bad (e.g., 'pushy parents'), and provides a more rounded description of the challenges of dealing with overuse injuries in youth sport. It also adopts an innovative form of representation to reach and impact non-academic audiences.